The epithelial barrier-protecting properties of a soy hydrolysate. Issue 8 (1st August 2018) - Kiewiet, Mensiena B. G.; González Rodríguez, Martín I.; Dekkers, Renske; Gros, Marjan; Ulfman, Laurien H.; Groeneveld, Andre; de Vos, Paul; Faas, Marijke M.
Abstract : A soy hydrolysate protects the epithelial cell layer from an increase in permeability in a barrier disruptor specific manner. Abstract : Enhancing the epithelial barrier function could be a possible strategy to prevent food allergy or reduce its symptoms. Soy hydrolysates containing bioactive peptides could be instrumental in this. In this study, the protective effects of pretreatment with 6 soy hydrolysates on calcium ionophore A23187-induced TEER reduction were studied in T84 cells. The effects of the most potent soy hydrolysate on tight junction gene expression were studied. In order to identify the underlying pathways involved, the barrier disruptor specificity of the effect was studied by comparing the protective effects on TEER and Lucifer Yellow flux after the exposure to barrier disruptors that work via different intracellular pathways, i.e. the disruptors A23187, mellitin, and deoxynivalenol (DON). Preincubation with one of the six hydrolysates protected the epithelial cells from a decrease in TEER induced by A23187 (restored to 105% of the starting point, while A23187 alone decreased to 53% of the starting value) and mellitin (restored to 11% of the starting point, while mellitin alone decreased to 3.8% of the starting value). This soy hydrolysate was found to increase claudin-1 and decrease claudin-2 expression. The protective effect of the hydrolysate on TEER was specific for the barrier disruptors A23187 and mellitin, but was not observed for DON. This observation suggests that the soy hydrolysate may act via PKC isoforms, which are known to lead to changes in the expression of claudin-1 and 2 . Our data suggest that specific soy hydrolysates may be designed to strengthen the epithelial barrier which might be instrumental in the management of the barrier function in individuals at risk of developing food allergy.